ANALGETIC EFFECT OF COMBINATION 3:2:1 GEL EXTRACT Ageratum conyzoides Mussaenda frondosa) AND Curcuma domestica of Staphylococcus aureus INFECTED POST PARTUM MICE - Hujjatusnaini, Noor; Nada, Ara Aulia; Jumrodah, Jumrodah; Nirmalasari, Ridha; Amin, Astuti Muh (Universitas Aisyah Pringsewu, 2023)
The lack of knowledge about Ageratum conyzoides, Mussaenda frondosa, and Curcuma domestica as alternative medicines for treating postpartum infections, because there is still little research and documentation being carried out. Therefore, this research is expected to prove in vivo in order to know the analgesic effect of the combination formulation 3:2:1 extracts of Ageratum conyzoides, Mussaenda frondosa, and Curcuma domestica as therapy for post-partum infections. The research method used a true experimental post-test only control-group design, with 36 pregnant female mice as the test object. Ageratum conyzoides leaves, Mussaenda frondosa, and Curcuma domestica were prepared in a 3:2:1 formulation, with design levels of 40%, 60% and 80%. Analgesic-effect data were analyzed using the ANAVA statistical method and Duncan's test with a significant level of 1%. The results of the analgesic effect were obtained from the average number of S.aureus colonies and the vaginal mucosal fluid secretion index of mice infected with S.aureus. The results showed that the combination formulation of 3:2:1 extracts with a concentration of 30% had a significant effect on growth in S.aureus at a significant level of 1%. It was concluded that the 3:2:1 combination formulation can be recommended as the most effective in inhibiting infection S.aureus.